Rational designed novel TiO2-x/Bi6Cr2O15/Bi quantum dots: Bi-based plasmonic photocatalysts for boosted detoxifying organic and inorganic wastewaters under visible light - Salmanzadeh-Jamadi, Zahra; Habibi-Yangjeh, Aziz; Khataee, Alireza; Kudaibergenov, Nurbolat (Elsevier, 2023)
We combined brown TiO2-x with Bi6Cr2O15 and Bi using a facile procedure to fabricate Bi-based plasmonic TiO2x/Bi6Cr2O15/Bi photocatalysts for detoxifying organic and inorganic wastewaters upon visible light. The TEM and HRTEM analyses provided strong evidence for the construction of quantum dots of the photocatalyst with diameter of almost 8.2 nm and intimate contact among TiO2-x, Bi6Cr2O15, and Bi components. The TiO2-x/ Bi6Cr2O15/Bi nanocomposites exhibited boosted activity in the degradation of tetracycline (TC), azithromycin (Azi), rhodamine B (RhB), methylene blue (MB), and photoreduction of Cr (VI) pollutants, and the performance was 12.9, 1.67, 10.4, 3.50, and 6.91-folds greater than TiO2-x, and 19.1, 1.60, 3.44, 2.88, and 1.90-times higher than Bi6Cr2O15 photocatalysts, respectively. In particular, h thorn and & BULL;OH species were identified as the key species involved in the TC degradation reaction. The electrochemical analyses, including EIS, Bode plots and photocurrent density, and PL spectroscopy exhibited efficacious segregation and transportation of charge carriers within the ternary photocatalyst. Finally, the biocompatibility of TC-treated solution over the TiO2-x/Bi6Cr2O15/ Bi photocatalyst was verified by the growth of lentil seeds.
Keywords: BrownTiO2-x; Plasmonic photocatalyst; Metallic Bi; Quantum dots; Biocompatibility